REPARATION OF THE MORAL PREJUDICES IN ROMANIAN LABOR LAW - AURELIAN GABRIEL ULUITU; IOANA PĂDURARIU (Challenges of the Knowledge Society)
Recent decisions issued by national labor Courts contain interesting references to the problem of the moral prejudices’ reparation (especially suffered by the employee). During the application of Romanian Labor Code – Law no. 53/20031, the Courts offered a poor practice regarding the above mentioned problem. Usually, the employees’ claims having as object the material reparation of a moral prejudice caused by the employers were rejected. The Courts considered that the claims were not founded, because the employees did not prove the irregularity and/or the existence of a moral prejudice. The present paper is trying to identify the situations (as categories) which confer to the employees the right to ask for the moral prejudices’ (material) reparation and the procedural mechanism in order to obtain a favorable solution (especially from the proves necessity point of view).